A case of denosumab-associated hyperparathyroidism: A differential diagnostic challenge - Emin Taşkıran; Sevnaz Şahin; Sumru Savaş; Zeliha Fulden Saraç; Selahattin Fehmi Akçiçek (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2021)
Denosumab is a relatively new medicine that has become the second option in the treatment of biphosphonate-resistant or intolerant osteoporosis. Subcutaneous injection with 6-month intervals, approval of its usage in stage 3-4 CKD and not having gastrointestinal side effects are advantages of denosumab. However, it has some disadvantages like requiring monitoring serum levels of calcium and vitamin D before each injection.